JEAN-PAUL SARTRE'S ANTOINE ROQUENTIN: AN EXISTENTIAL SUCCESSOR OF RUSSIAN SUPERFLUOUS MAN - Kopecny, Pavel (Bohemica Olomucensia, 2021)
The study confronts the concept of the superfluous man, as it appeared in 19th century Russian literature, with the features used in French existentialism. Specifically, we will deal with the analysis of Antoine Roquentin, protagonist of Jean-Paul Sarter's Nausea (1938).
Keywords: absurd hero; existential hero; French existential literature; Jean-Paul Sartre; Roquentin; Russian literature; the superfluous man